Comparative Analysis of Clinical and Pathological Characteristics of Breast Cancer among Premenopausal and Postmenopausal Women: Breast Cancer among Premenopausal and Postmenopausal Women - Gardezi, Syed Saad; Shakeel, Mehroosh; Ullah, Muhammad Sami; Nisar, Bushra; Asif, Muhammad; Ashraf, Muhammad (Pakistan Journal of Health Sciences, 2025)
Breast cancer shows distinct clinical and pathological characteristics between premenopausal and postmenopausal women, potentially affecting disease progression and treatment outcomes. Understanding these differences is essential for optimizing management strategies. Objectives: To compare the clinical and pathological characteristics of breast cancer among premenopausal and postmenopausal women. Methods: This retrospective study was conducted at the Department of Histopathology, Quaid-e-Azam Medical College, Bahawalpur, from January to December 2024. A total of 188 breast cancer patients (94 premenopausal, 94 postmenopausal) were included. Clinical variables such as age at diagnosis, family history, tumor laterality, clinical stage, lymph node involvement, and metastasis were analyzed, along with pathological features like histological type, tumor grade, molecular subtype, and hormone receptor status. Data were analyzed using a t-test and a chi-square test. Results: The mean age at diagnosis was significantly lower in premenopausal women (46.96 ± 5.29 years) compared to postmenopausal women (65.87 ± 10.82 years) (p<0.001). A positive family history was more common among premenopausal patients (37.2% vs. 23.4%, p=0.039). Lymph node involvement was higher in premenopausal women (73.4% vs. 59.6%, p=0.045). Tumor laterality, clinical stage, metastasis, histological type, tumor grade, molecular subtype, and hormone receptor status were similar between groups (p>0.05). Conclusions: It was concluded that premenopausal women presented at a younger age, with more frequent family history and lymph node involvement, suggesting a potentially aggressive disease course. However, pathological tumor characteristics were comparable. Early detection and genetic risk assessment are crucial, particularly in younger women.